Viral-Targeted Strategies Against EBV-Associated Lymphoproliferative Diseases - Hui, Kwai Fung; Yiu, Stephanie Pei Tung; Tam, Kam Pui; Chiang, Alan Kwok Shing (Frontiers in Oncology, 2019)
Epstein-Barr virus (EBV) is strongly associated with a spectrum of EBV-associated lymphoproliferative diseases (EBV-LPDs) ranging from post-transplant lymphoproliferative disorder, B cell lymphomas (e.g. endemic Burkitt lymphoma, Hodgkin lymphoma and diffuse large B cell lymphoma) to NK or T cell lymphoma (e.g. nasal NK/T-cell lymphoma). The virus expresses a number of latent viral proteins which are able to manipulate cell cycle and cell death processes to promote survival of the tumor cells. Several FDA-approved drugs or novel compounds have been shown to induce killing of some of the EBV-LPDs by inhibiting the function of latent viral proteins or activating the viral lytic cycle from latency. Here, we aim to provide an overview on the mechanisms by which EBV employs to drive the pathogenesis of various EBV-LPDs and to maintain the survival of the tumor cells followed by a discussion on the development of viral-targeted strategies based on the understanding of the patho-mechanisms.